2003
DOI: 10.1128/ec.2.1.49-61.2003
|View full text |Cite
|
Sign up to set email alerts
|

Cell Biology of Mating inCandida albicans

Abstract: It was recently demonstrated that strains homozygous for either of the mating type-like loci MTLa and MTL␣ of Candida albicans undergo white-opaque switching and that expression of the opaque-phase phenotype greatly enhances mating between strains. Exploiting the latter property to obtain high-frequency mating, we have characterized the cell biology of the mating process of C. albicans. Employing continuous videomicroscopy, computer-assisted three-dimensional reconstruction of living cells, and fluorescence mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
218
2
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 136 publications
(230 citation statements)
references
References 35 publications
9
218
2
1
Order By: Relevance
“…Opaque cells of the mutants ste2⌬ and ste4⌬ were also compared with opaque cells of parent strain P37005 for their ability to mate with opaque cells of the ␣/␣ strain WO-1, by using microscopically identified fusion as an assay (Lockhart et al, 2003a) Together with the pheromone response data, these results indicated that the ␣-pheromone receptor,Ste2p and the ␤-subunit of the heterotrimeric G protein Ste4p were essential for ␣-pheromone-induced shmooing and fusion of opaque a/a cells, and that the a-pheromone receptor Ste3p was essential for a-pheromone-induced shmooing and fusion of opaque ␣/␣ cells.…”
Section: Opaque Cell Pheromone Response Of Ste2⌬ Ste3⌬ and Ste4⌬mentioning
confidence: 99%
See 4 more Smart Citations
“…Opaque cells of the mutants ste2⌬ and ste4⌬ were also compared with opaque cells of parent strain P37005 for their ability to mate with opaque cells of the ␣/␣ strain WO-1, by using microscopically identified fusion as an assay (Lockhart et al, 2003a) Together with the pheromone response data, these results indicated that the ␣-pheromone receptor,Ste2p and the ␤-subunit of the heterotrimeric G protein Ste4p were essential for ␣-pheromone-induced shmooing and fusion of opaque a/a cells, and that the a-pheromone receptor Ste3p was essential for a-pheromone-induced shmooing and fusion of opaque ␣/␣ cells.…”
Section: Opaque Cell Pheromone Response Of Ste2⌬ Ste3⌬ and Ste4⌬mentioning
confidence: 99%
“…Opaque cells of the mutants ste2⌬ and ste4⌬ were also compared with opaque cells of parent strain P37005 for their ability to mate with opaque cells of the ␣/␣ strain WO-1, by using microscopically identified fusion as an assay (Lockhart et al, 2003a) observed between opaque ste2⌬ or ste4⌬ cells, and opaque WO-1 cells ( Figure 3, B and C, respectively; and K). Opaque cells of the complemented strains ste2⌬/STE2 and ste4⌬/ STE4 regained the capacity to mate with opaque WO-1 cells (data not shown).…”
Section: Opaque Cell Pheromone Response Of Ste2⌬ Ste3⌬ and Ste4⌬mentioning
confidence: 99%
See 3 more Smart Citations